(untitled) (Principles and Practice of Clinical Research, 2018)
Course Description: This course is aimed at students of various levels of training, from medical students to practicing epileptologists and other clinical practitioners; it progresses from a basic to a more advanced level. It will walk students through the diagnosis of medically intractable epilepsy, the mechanisms believed to underlie medical intractability, existing diagnostic modalities, as well as the available management techniques and the science behind them. The course is composed of mini-modules with the main mini-modules explaining basic concepts, followed by testing to encode these basic concepts and to connect them with more advanced concepts in a meaningful way. Bonus modules will help students develop a deeper understanding of more advanced concepts; they will also help target important concepts for professionals in various specialties, and push students toward a deeper understanding of the subject matter. While this course can be taken on students’ own time at any time during the year, they will have the opportunity to interact with current students and alumni on the forums, to discuss topics with students at different levels of training, and to raise questions that may lead to future collaboration.